2017
DOI: 10.2196/mental.8168
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Exploration of the Potential for Adverse Events When Using an Online Peer Support Network for Mental Health: Cross-Sectional Survey

Abstract: BackgroundOnline peer support networks are a growing area of mental health support for offering social connection, identity, and support. However, it has been reported that not all individuals have a positive experience on such networks. The potential for adverse events within a moderated online peer support network is a new area of research exploration.ObjectiveThe objective of the study was to determine if use of an online moderated peer networks leads to adverse events for users.MethodsFour biannual online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Against this backdrop, it is essential to develop evidence-based social media–enabled interventions that promote social support while ensuring safety and diminishing harmful consequences. A number of studies from our research lab [ 42 - 44 , 55 ] and others [ 39 ] have shown that carefully designed moderated web-based social media interventions can be safely implemented and are not associated with harmful effects. This study adds to this growing body of evidence by demonstrating that web-based social media interventions can be safely deployed to help-seeking young people via a national web counseling service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Against this backdrop, it is essential to develop evidence-based social media–enabled interventions that promote social support while ensuring safety and diminishing harmful consequences. A number of studies from our research lab [ 42 - 44 , 55 ] and others [ 39 ] have shown that carefully designed moderated web-based social media interventions can be safely implemented and are not associated with harmful effects. This study adds to this growing body of evidence by demonstrating that web-based social media interventions can be safely deployed to help-seeking young people via a national web counseling service.…”
Section: Discussionmentioning
confidence: 99%
“…That said, the type and function of online peer support groups and SNS appear to have a significant effect on their outcomes. For example, unmoderated forums and SNS can lead to increased contagion, distress, and collusion among users [ 39 ]. Conversely, SNS interventions that have been moderated, ideally by professionals, have been found to be safe, engaging, supportive, and useful [ 39 , 41 - 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These elements could be optional and be offered based on the individual’s use patterns. Finally, although the tendency has been to remove graphic, or potentially triggering, content from platforms, there have been discussions about the dangers of overmoderation [ 79 , 81 , 82 ] and the benefits of self-expression [ 83 ]. Our findings suggest a need to consider safe ways of moderating content while also allowing free expression.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of online peer support groups and social networking sites (SNS) exist for people with mental health problems. Overall, the extant evidence suggests that online peer support groups can foster a sense of social connectedness, empowerment, and improved quality of life as well as reduce depression and emotional distress [38][39][40]. That said, the type and function of online peer support groups and SNS appear to have a significant effect on their outcomes.…”
Section: Introduction Backgroundmentioning
confidence: 99%